2002
DOI: 10.1021/ie020034a
|View full text |Cite
|
Sign up to set email alerts
|

Free-Volume Activity Coefficient Models for Dendrimer Solutions

Abstract: The ability of the Unifac-FV and Entropic-FV models to predict phase equilibria for dendrimer systems is investigated in this work. Different approaches are considered for the estimation of the density of the dendrimers, which is required as input parameter in the free-volume models. The density is not always available for such polymers.The predictions obtained by the two models are compared with recent vapor-liquid equilibrium experimental data for dendrimer systems. It is shown in this study that both method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…The formed adsorbed layers had thicknesses that were 51%, 37% and 43% of the corresponding diameters predicted using the hydrodynamic radii in Table , respectively. The neutron reflectivity data were further evaluated using the molecular volumes of 5149 Å 3 for G2, 22481 Å 3 for G4 and 91803 Å 3 for G6 (obtained using the dendrimer density of 1.2 g cm −3 Table ), which showed that the number of adsorbed particles ( N ) decreased for higher generations as the average dendrimer molecular area (including solvent, A m ) increased. With an accurate determination of N , the dendrimer surface excess (Γ) could then be calculated.…”
Section: Resultsmentioning
confidence: 99%
“…The formed adsorbed layers had thicknesses that were 51%, 37% and 43% of the corresponding diameters predicted using the hydrodynamic radii in Table , respectively. The neutron reflectivity data were further evaluated using the molecular volumes of 5149 Å 3 for G2, 22481 Å 3 for G4 and 91803 Å 3 for G6 (obtained using the dendrimer density of 1.2 g cm −3 Table ), which showed that the number of adsorbed particles ( N ) decreased for higher generations as the average dendrimer molecular area (including solvent, A m ) increased. With an accurate determination of N , the dendrimer surface excess (Γ) could then be calculated.…”
Section: Resultsmentioning
confidence: 99%
“…The group contribution method UNIFAC-FV model [34,[44][45][46] allows for the prediction of the solubility behaviour and the mass-fraction activity coefficient at infinite dilution, X 1 13;pred . According to UNIFAC-FV, the prediction in the systems with hyperbranched or dendritic polymers assumes the structure of the poly-FIGURE 2.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental results on the phase behavior and density data offer a database for the theoretical researchers to develop and test suitable thermodynamic models to predict the solution behavior of hyperbranched polymer systems. Earlier modeling work includes Monte Carlo simulation by Lue [64] and Timoshenko and Kuznetsov [65], molecular dynamics method by Steinhauser [66], lattice cluster theory (LCT) modeling by Jang, et al [45,[67][68][69][70][71], universal functional activity coefficients-free-volume (UNIFAC-FV) method by Kouskoumvekaki, et al [72] and Seiler, et al [47], etc., which have been reviewed by Seiler [7]. In the past eight years after the review, more models have been developed for hyperbranched polymer systems accompanied with a deeper understanding of the hyperbranched polymer architecture and an increasing number of low-pressure and high-pressure experimental data.…”
Section: Thermodynamic Modelingmentioning
confidence: 99%